Knowledge and Practice of Family Planning Methods among Married Women of Reproductive Age of Chepang Community of Dhading District - Panta, Prem Prasad; Tripathi, Prativa; Amgain, Kapil; Sharma, Deepak (Journal of Karnali Academy of Health Sciences, 2020)
Background: Knowledge of family planning plays a significant role in public health to control birth and maintain the health of women. The Chepang, a backward and deprived indigenous group of Nepal, heavily experiences teenage pregnancies, high fertility and high mortality of infants and mothers, which are largely due to lack of knowledge on family planning. So, the objective of this study was to find knowledge and practice regarding family planning among married women of reproductive age. Methods: A cross sectional descriptive study was conducted among married women of the Chepang community, Benighat, Dhadnig, Nepal from September 2016 to November 2016. A simple random probability sampling technique was used to collect 80 respondents. Results: The mean age of the respondents was (30.7 ± 7) years, ranging from 17 to 47, with majority being 25-29 years.. The average marital age, and average age at first pregnancy were (16.7 ± 2) years and (17.7 ± 2.33) years respectively. Ninety-two percent of the respondents were aware of family planning. The major sources of information were health workers (79.2%) and radio/television (57.1%). The most known methods of contraception were Depo- provera (87.3%) and pills (85.7%), whereas least known methods were copper T (31%) and Norplant (31%). The contraceptive prevalence was 49.9%, among which pills and Depo provera were used maximum by the respondents (41.1%). One third (33.8%) of the respondents had the adequate knowledge. Education, spousal communication, current contraceptive users, married age, number of children, and age at first pregnancy were the significant factors affecting the knowledge and practice of family planning (P < 0.05). Conclusion: Literacy status, spousal communication, marital age, size of children, and age at first pregnancy are the associated factors of knowledge. Whereas, practicing of family planning was associated to cultural taboos, self-decision, literacy status, and spousal communication.